Palladium‐Catalyzed Direct α‐Arylation of Arylacetonitriles with Aryl Tosylates and Mesylates. Issue 12 (9th March 2020) - Yuen, On Ying; Chen, Xiangmeng; Wu, Junyu; So, Chau Ming
Abstract : The first general palladium‐catalyzed α‐arylation of arylacetonitriles with aryl and heteroaryl sulfonates are reported. Pd(OAc)2 associated with XPhos serves as the effective catalyst to facilitate this reaction. A broad range of electron‐rich, ‐neutral, ‐deficient, and sterically hindered aryl/heteroaryl tosylates and mesylates are coupled with arylacetonitriles bearing different substituents to give the corresponding products in good to excellent yields. Catalyst loading down to 0.1 mol‐% Pd was achieved, and 22 unprecedented compounds were synthesized from 43 demonstrated examples using this method. Its applicability with the modification of biological phenolic compounds was successfully demonstrated. The Pd/XPhos system catalyzed the α‐arylation and followed by alkylation in one‐pot sequential conditions, resulting in the direct synthesis of compounds containing quaternary center‐ and deuterium‐containing compounds in good to excellent yields. Abstract : The first general palladium‐catalyzed α‐arylation of arylacetonitriles with aryl and heteroaryl sulfonates are reported. The catalyst system comprising of Pd(OAc)2 and XPhos is highly effective towards this reaction. A wide range of aryl/heteroaryl tosylates and mesylates are coupled with arylacetonitriles smoothly and catalyst loadings as low as 0.1 mol‐% Pd can be achieved.